'They are my future': childbearing desires and motivations among women with disabilities in Ghana - implications for reproductive healthcare - John Kuumuori Ganle; Rebecca Racheal Apolot; Tafadzwa Rugoho; Joshua Sumankuuro (BMC, 2020)
Abstract Background Previous research has highlighted widespread public mis/perceptions that portray women with disabilities (WWDs) as asexual, less likely to marry, and often not interested in childbearing. However, evidence from high-income settings shows that many WWDs are sexually active and do have or want to have children. Notwithstanding this, very few studies have focused on understanding childbearing desires and motivations among WWDs in low-income settings. This qualitative research explored childbearing desires and motivations among WWDs in Ghana. Methods A cross-sectional qualitative study was conducted with WWDs aged 18-49 years in Northern Ghana. The distribution of participants by disability types were as follows: physical disability/impairment (n = 37); visual impairment (n = 11); speech and hearing impairment (n = 14); epilepsy (n = ten); and albinism (n = five). A pre-tested open-ended thematic topic guide was designed and used to conduct in-depth interviews. Interviews were tape-recorded and later transcribed for analysis. Transcripts were coded using QSR NVivo 11 software. Thematic content analysis techniques were used to analyse and present the data. Results Nearly all the WWDs interviewed were sexually active, desiring to have children, and intended to have as many children as they could support. Strong desire to experience the joy of motherhood; fear of social insecurity; fear of old age economic insecurity; desire to challenge stigma and negative stereotypes about disability, sexuality and motherhood; and desire for self-actualisation, were key motivations for childbearing. Conclusion Our findings challenge existing negative public perceptions about the status of WWDs in relation to sexuality, childbearing and motherhood. More importantly, our findings suggest that if the Sustainable Development Goals related to universal access to sexual and reproductive healthcare are to be attained, WWDs must be targeted with quality sexual and reproductive healthcare information and services.